Traditional Chinese Medicine ointment massage therapy and nursing care for a patient with lumbar disc herniation (中药膏摩治疗腰椎间盘突出症1例的护理体会) - CHEN Jinling (陈金铃); LIU Jie (刘洁); ZHANG Ping (张聘); DONG Yuxia (董玉霞) (中西医结合护理)
This paper reviewed the clinical effect of Traditional Chinese Medicine (TCM) ointment massage therapy and nursing care for a patient with lumbar disc herniation. Based on the routine care and health education, the TCM ointment massage therapy was adopted to relieve the lower extremity pain and weakness. TCM ointment massage therapy is considered as an effective and well-accepted treatment of lumbar disc herniation. (本文回顾中药膏摩的治疗1例腰椎间盘突出症患者的效果, 总结护理经验。在常规护理和健康宣教的基础上, 通过实施中药膏摩技术, 能够有效改善患者疼痛和下肢无力的症状。中药膏摩治疗腰椎间盘突出症效果明显, 不良反应少, 易被患者接受。)